SELF IDENTITY AND RELIGIOSITY OF MADURESE PEOPLE: INDIGENOUS CONCEPTS BASED ON THE PERSPECTIVE OF MADURESE YOUTH: religiousity Indigenous Concepts Based on the Perspective of Madurese Youth - Rahmasari, Diana; Darmawanti, Ira (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to explain the identity and religiosity of the Madurese based on the perspective of Madurese teenagers. The concept of identity and religiosity refers to the concept of indigenous or local wisdom of Madurese culture. This study uses a qualitative method with a descriptive approach in explaining the research study. The Sources of data used in this study are primary and secondary data sources. Sources of primary data were obtained directly from Madurese youth using FGD and semi-structured interviews with 7 students of class X in Pamekasan Regency. Each student meets the requirements of being born and raised in Madura and his parents are Madurese. While the secondary data sources are data obtained from the study of books, literature, and the results of previous research on the Madurese which have relevance to the focus of this research. Interviews with Madurese cultural observers were conducted to complete primary and secondary data as a triangulation of data sources, especially to obtain information on the concept of religiosity and identity indigenously or by referring to the local wisdom of Madurese culture. The analysis of the results of the study explains that being a Madurese is having high self-esteem, of course, self-esteem in the indigenous Madurese concept, namely ajina aba